Controlling Chaos and Bifurcation of Subsynchronous Resonance in Power System - Harb, A. M.; Widyan, M. S. (Nonlinear Analysis: Modelling and Control, 2002)
Linear and nonlinear state feedback controllers are proposed to control the bifurcation of a new phenomenon in power system, this phenomenon of electro-mechanical interaction between the series resonant circuits and torsional mechanical frequencies of the turbine generator sections, which known as Subsynchronous Resonance (SSR). The first system of the IEEE second benchmark model is considered. The dynamics of the two axes damper windings, Automatic Voltage Regulator (AVR) and Power System Stabilizer (PSS) are included. The linear controller gives better initial disturbance response than that of the nonlinear, but in a small narrow region of compensation factors. The nonlinear controller not only can be easily implemented, but also it stabilizes the operating point for all values of the bifurcation parameter.